Crime and social justice in Indian country - Nielsen, Marianne O.; Jarratt-Snider, Karen (Indigenous justice., 2018)
"Crime and Social Justice in Indian Country calls to attention the need for culturally appropriate research protocols and critical discussions of social and criminal justice in Indian Country. The contributors come from the growing wave of Native American as well as non-Indigenous scholars who employ these methods. They reflect on issues in three key areas: crime, social justice, and community responses to crime and justice issues. Topics include stalking, involuntary sterilization of Indigenous women, border-town violence, Indian gaming, child welfare, and juvenile justice. These issues are all rooted in colonization; however, the contributors demonstrate how Indigenous communities are finding their own solutions for social justice, sovereignty, and self-determination."--Provided by publisher.